Akta A324 Criminal Procedure Code (Amendment And Extension) Act, 1976 - Ibrahim, Ahmad (Journal of Malaysian and Comparative Law, 2018)
Akta A324 Criminal Procedure Code (Amendment And Extension) Act, 1976